Do Rural Firms Perceive Different Problems? Geography, Sorting, and Barriers to Growth in UK SMEs. (February 2015) - Lyee, Neil; Cowling, Marc
Support for small businesses is often delivered separately for urban and rural areas, based on the idea that the barriers to business growth differ geographically. Yet firms in rural and urban areas will also differ in their characteristics, and these may be more important influences on firm growth than location. In this paper we test whether firms in urban, semirurals, and rural areas perceive each of eight obstacles to their success differently, based on a large sample of UK SMEs. After controlling for selection effects, rural and semirural firms are more likely to perceive regulation as a problem while rural firms are more likely to see the economy as an obstacle to success. We also find some evidence that skills shortages may be more acute for rural firms, once selection effects are controlled for. The results provide only limited support for geographically differentiated policy for small businesses.